2019
DOI: 10.1111/risa.13306
|View full text |Cite
|
Sign up to set email alerts
|

Residents’ Reactions to Earthquake Early Warnings in Japan

Abstract: This article empirically examines the effectiveness of earthquake early warning (EEW) in Japan based on experiences of residents who received warnings before earthquake shaking occurred. In Study 1, a survey (N = 299) was conducted to investigate residents’ experiences of, and reactions to, an EEW issued in Gunma and neighboring regions on June 17, 2018. The main results were as follows. (1) People's primary reactions to the EEW were mental, not physical, and thus motionless. Most residents stayed still, not f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
72
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(78 citation statements)
references
References 22 publications
6
72
0
Order By: Relevance
“…In Japan, most of the literature shows that residents of the country agree with the implementation of EEW and find it useful. However, Nakayachi et al (2019) highlight that this is not always the case. In some regions of the country, the public does not believe that EEW alerts are effective, given their lack of detailed information about the strength of the incoming ground shaking and the expected arrival time.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…In Japan, most of the literature shows that residents of the country agree with the implementation of EEW and find it useful. However, Nakayachi et al (2019) highlight that this is not always the case. In some regions of the country, the public does not believe that EEW alerts are effective, given their lack of detailed information about the strength of the incoming ground shaking and the expected arrival time.…”
Section: Discussionmentioning
confidence: 94%
“…The results of the survey indicated that 87% of the respondents were familiar with EEW systems and found them useful (Fujinawa and Noda, 2013). Positive public reaction and agreement toward EEW implementations in Japan can be also found in Hoshiba (2014), Nakayachi et al (2019), and Santos-Reyes (2019). In addition, Fujinawa and Noda (2013) highlighted that the warning issued during the 2011 minor tremor provided people with a valuable chance to prepare for the strong incoming shaking.…”
Section: Social and Behavioral Spherementioning
confidence: 90%
See 2 more Smart Citations
“…In a recent study, Nakayachi et al (2019) noted that ''despite significant evidence of the utility of EEW for technical applications, there is limited information on the actual (not potential) effectiveness of EEW for personal protection'' (p. 2) and that ''how effective it actually is in practice is not yet clear.' 'Nakayachi et al (2019) concluded that primary reactions were passive in nature, and that the overwhelming majority of survey respondents stated that EEW enabled them to mentally prepare for shaking rather than to take action. Their study supports the notion that EEW can provide important emotional preparedness prior to shaking.…”
Section: Personal (And Emotional) Comfortmentioning
confidence: 99%